Method for preparing latex composition for dip molding
By adding starch to the nitrile copolymer latex, the content of emulsifier is reduced and the polymerization stability is improved, and the foam and quality problems caused by excessive emulsifier are solved, and the excellent mechanical properties and polymerization stability of the gloves are achieved.
Patent Information
- Application Number
- CN202210568772.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-27
- Filing Date
- 2022-05-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-05-24
AI Technical Summary
In the polymerization process of nitrile copolymer latex, excessive use of emulsifiers leads to foam generation, product quality decline, and may cause viscosity and slippage, affecting the mechanical stability and polymerization stability of the gloves.
By adding starch as an additive to the preparation of nitrile copolymer latex, the content of emulsifier is reduced, and the starch adsorbed on the surface of the particles during the polymerization process increases repulsion force to prevent particles from aggregating, thereby improving mechanical stability and polymerization stability.
It has achieved the reduction of emulsifier content in nitrile copolymer latex, improved mechanical stability and polymerization stability, reduced foam generation, improved tensile strength and elongation of gloves, and improved product quality.
Smart Images

Figure BDA0003658285490000121 
Figure BDA0003658285490000141 
Figure BDA0003658285490000151
Abstract
Description
Technical Field
[0001] The present specification relates to a latex composition for dip molding, a method for preparing the same, and a dip-molded article prepared therefrom. Background Art
[0002] The main raw material of gloves used in medical, agricultural and livestock product processing and industrial applications is natural rubber latex. However, when gloves made of natural rubber latex are used, since natural rubber latex contains protein, the problem of contact allergy often occurs to the glove wearer. Therefore, attempts have been made to use protein-free synthetic rubber latex such as nitrile copolymer latex to manufacture gloves.
[0003] The nitrile copolymer latex is prepared by emulsion polymerization. The emulsifier (surfactant) used in the emulsion polymerization process plays the role of providing polymerization sites and maintaining particle stability. It is well known that in conventional emulsion polymerization processes, when the amount of anionic emulsifier used is about 3phm to 5phm (parts per hundred parts monomer), a latex with excellent polymerization stability, particle size, mechanical stability and storage stability of the polymer can be obtained.
[0004] However, the use of emulsifiers may generate excessive foam during the glove manufacturing process, resulting in pinholes, which may reduce product quality and generate a large amount of wastewater containing emulsifiers. In addition, when the emulsifier remains on the gloves, it may cause stickiness and other problems, resulting in a decrease in product properties. When the user wears the gloves and comes into contact with water, problems such as foam or slipping may occur. Summary of the invention
[0005] Technical issues
[0006] The description of this specification is used to solve the prior art problems as described above. One purpose of this specification is to provide a method for preparing a latex composition for dip molding, wherein the latex composition for dip molding reduces the content of emulsifier used in the nitrile copolymer latex polymerization process and has excellent mechanical stability and polymerization stability.
[0007] Another object of the present specification is to provide a latex composition for dip molding and a dip-molded product prepared therefrom, wherein the latex composition for dip molding has excellent mechanical properties and quality such as tensile strength and elongation.
[0008] Means of solving the problem
[0009] According to one aspect, a method for preparing a latex composition for dip molding is provided, which comprises: step (a), preparing a monomer mixture comprising a conjugated diene monomer, an ethylenically unsaturated nitrile monomer and an ethylenically unsaturated acid monomer; step (b), adding an additive comprising an inorganic solvent, an emulsifier and starch to the monomer mixture; and step (c), preparing a copolymer latex by polymerizing the monomer mixture, wherein the content of the starch is 0.1 to 4.9 parts by weight relative to 100 parts by weight of the monomer mixture.
[0010] In one embodiment, the conjugated diene monomer may be one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, isoprene, and a combination of two or more thereof.
[0011] In one embodiment, the ethylenically unsaturated nitrile monomer may be one selected from the group consisting of acrylonitrile, methacrylonitrile, fumaric acid nitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, and a combination of two or more thereof.
[0012] In one embodiment, the ethylenically unsaturated acid monomer may be one selected from the group consisting of methacrylic acid, acrylic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, citraconic anhydride, styrene sulfonic acid, monobutyl fumarate, monobutyl maleate, mono-2-hydroxypropyl maleate, and a combination of two or more thereof.
[0013] In one embodiment, the emulsifier may be an ionic surfactant.
[0014] In one embodiment, the emulsifier may be one selected from the group consisting of alkylbenzene sulfonate, alkyl diphenyl ether disulfonate, aliphatic sulfonate, higher alcohol sulfate, α-olefin sulfonate, alkyl ether sulfate, and a combination of two or more thereof.
[0015] In one embodiment, the emulsifier may include sodium dodecylbenzenesulfonate and disodium alkyl diphenyloxide sulfonate.
[0016] In one embodiment, the content of the emulsifier may be 0.1 parts by weight to 2.9 parts by weight relative to 100 parts by weight of the monomer mixture.
[0017] In one embodiment, the starch may be one selected from the group consisting of natural starch, a derivative of the natural starch, amylose extracted from the natural starch, modified starch, dextrin, and a combination of two or more thereof.
[0018] In one embodiment, the dextrose equivalent value of the dextrin may be 8-22.
[0019] In one embodiment, the content of the starch may be 0.25 to 2 times the content of the emulsifier.
[0020] According to still another aspect, a latex composition for dip molding produced by the method for producing the latex composition for dip molding is provided.
[0021] According to another aspect, there is provided a dip-molded article produced by dip-molding the above-mentioned latex composition for dip molding.
[0022] In one embodiment, the dip-molded product may be one selected from the group consisting of medical gloves, agricultural and livestock product processing gloves, and industrial gloves.
[0023] Effects of the Invention
[0024] The method for preparing a latex composition for dip molding according to one aspect of the present specification is environmentally friendly by reducing the content of the emulsifier used in the polymerization process of the nitrile copolymer latex, and has excellent mechanical stability and polymerization stability, so it can be applied to the preparation of a stable latex composition for dip molding.
[0025] The latex composition for dip molding according to another aspect of the present specification and the dip molded product prepared therefrom have excellent mechanical properties and quality such as tensile strength and elongation, and can therefore be applied to the preparation of medical gloves, gloves for processing agricultural and livestock products, and industrial gloves.
[0026] The effects according to various aspects of the present specification are not limited to the above-described effects, and should be understood to include all effects inferred from the detailed description of the present invention or the structure of the invention described in the claims. DETAILED DESCRIPTION
[0027] The description of this specification can be implemented in many different forms and is therefore not limited to the embodiments described herein.
[0028] Throughout the specification, when a part is described as being "connected" to another part, it includes not only the case of "direct connection" but also the case of "indirect connection" with other components in between. In addition, the term "comprising" used in this article means that other components are not excluded but further include other components when there is no special contrary description.
[0029] In this specification, when describing a series of numerical ranges, unless otherwise specified in its specific range, these values have the precision of significant figures provided according to the standard rules in chemistry for significant figures. For example, 10 includes the range of 5.0 to 14.9, and the number 10.0 includes the range of 9.50 to 10.49.
[0030] Method for preparing latex composition for dip molding
[0031] According to one aspect of the present specification, a method for preparing a latex composition for dip molding may include: step (a), preparing a monomer mixture comprising a conjugated diene monomer, an ethylenically unsaturated nitrile monomer and an ethylenically unsaturated acid monomer; step (b), adding additives comprising an inorganic solvent, an emulsifier and starch to the above-mentioned monomer mixture; and step (c), preparing a copolymer latex by polymerizing the above-mentioned monomer mixture.
[0032] The content of the starch may be 0.1 to 4.9 parts by weight relative to 100 parts by weight of the monomer mixture. For example, the content of the starch may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 3.9, 4.4, 4.5, 4.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 3.4, 4.5 .4 parts by weight, 2.5 parts by weight, 2.6 parts by weight, 2.7 parts by weight, 2.8 parts by weight, 2.9 parts by weight, 3.0 parts by weight, 3.1 parts by weight, 3.2 parts by weight, 3.3 parts by weight, 3.4 parts by weight, 3.5 parts by weight, 3.6 parts by weight, 3.7 parts by weight, 3.8 parts by weight, 3.9 parts by weight, 4.0 parts by weight, 4.1 parts by weight, 4.2 parts by weight, 4.3 parts by weight, 4.4 parts by weight, 4.5 parts by weight, 4.6 parts by weight, 4.7 parts by weight, 4.8 parts by weight, 4.9 parts by weight, or a value between two of them. When the content of the starch is greater than 4.9 parts by weight relative to 100 parts by weight of the monomer mixture, mechanical properties such as tensile strength and elongation of the molded product and product quality may be reduced.
[0033] The step (a) is a step of preparing a monomer mixture, wherein the monomer mixture comprises a conjugated diene monomer, an ethylenically unsaturated nitrile monomer and an ethylenically unsaturated acid monomer as monomers constituting the nitrile copolymer. The step (a) can be performed under a nitrogen atmosphere.
[0034] Based on the total weight of the monomer mixture, the monomer mixture may contain 50 to 98 weight percent of a conjugated diene monomer, 1 to 49 weight percent of an ethylenically unsaturated nitrile monomer, and 1 to 10 weight percent of an ethylenically unsaturated acid monomer. If the content of each monomer contained in the monomer mixture exceeds the above range, the molded article may become too soft or too hard, which may reduce the wearing feeling of the user of the dip-molded article or reduce the oil resistance of the dip-molded article, and may reduce the tensile strength.
[0035] The conjugated diene monomer may be one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, isoprene, and a combination of two or more thereof, for example, 1,3-butadiene, but not limited thereto.
[0036] The ethylenically unsaturated nitrile monomer may be one selected from the group consisting of acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethyl acrylonitrile, and a combination of two or more thereof, and may be, for example, acrylonitrile, but is not limited thereto.
[0037] The ethylenically unsaturated acid monomer may be one selected from the group consisting of methacrylic acid, acrylic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, citraconic anhydride, styrene sulfonic acid, monobutyl fumarate, monobutyl maleate, mono-2-hydroxypropyl maleate, and a combination of two or more thereof, and may be, for example, methacrylic acid, but is not limited thereto.
[0038] The above step (b) is a step of preparing emulsion polymerization by adding an additive comprising an inorganic solvent, an emulsifier and starch to the above monomer mixture. When starch is added, the starch is adsorbed on the surface of the particles in the polymerization step, thereby increasing the repulsive force between the particles and preventing the particles from aggregating with each other, and increasing the stability, thereby reducing the content of the emulsifier used in the polymerization of the nitrile copolymer latex.
[0039] The inorganic solvent may be water, for example, ion-exchanged water, but is not limited thereto.
[0040] The emulsifier may be an ionic surfactant, but is not limited thereto. For example, the emulsifier may be one selected from the group consisting of anionic surfactants, cationic surfactants, amphoteric surfactants, and a combination of two or more thereof.
[0041] The emulsifier may be one selected from the group consisting of alkylbenzene sulfonate, alkyl diphenyl ether disulfonate, aliphatic sulfonate, higher alcohol sulfate, α-olefin sulfonate, alkyl ether sulfate, and a combination of two or more thereof, but is not limited thereto.
[0042] The emulsifier may include sodium dodecylbenzene sulfonate. The sodium dodecylbenzene sulfonate has high solubility in water, low price and economic advantages, but will generate a lot of foam when used alone, reducing the chemical stability of latex.
[0043] The emulsifier may include disodium alkyl diphenyl ether sulfonate. By using disodium alkyl diphenyl ether sulfonate as an emulsifier, aggregation of monomers during polymerization can be prevented, thereby increasing the conversion rate of the polymerization reaction.
[0044] The emulsifier may include sodium dodecylbenzene sulfonate and disodium alkyl diphenyl ether sulfonate, but is not limited thereto. By using the emulsifier including sodium dodecylbenzene sulfonate and disodium alkyl diphenyl ether sulfonate, the coagulation of the monomer mixture and the starch can be prevented, the conversion rate of the polymerization reaction can be increased, and the mechanical stability, chemical stability and polymerization stability of the latex composition can be improved.
[0045] The weight ratio of the sodium dodecylbenzene sulfonate and the disodium alkyl diphenyl oxide sulfonate may be 1 to 3:1, but is not limited thereto. For example, the weight ratio of the sodium dodecylbenzene sulfonate and the disodium alkyl diphenyl oxide sulfonate may be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, or a ratio between two weight ratios thereof. When the weight ratio of the sodium dodecylbenzene sulfonate and the disodium alkyl diphenyl oxide sulfonate exceeds the above range, the conversion rate of the polymerization reaction may be reduced, and the mechanical stability may be reduced.
[0046] The content of the emulsifier may be 0.1 to 2.9 parts by weight relative to 100 parts by weight of the monomer mixture. For example, the content of the emulsifier may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, or a value between two of these values relative to 100 parts by weight of the monomer mixture. When the emulsifier content is less than 0.1 parts by weight relative to 100 parts by weight of the monomer mixture, the mechanical stability and polymerization stability may be reduced. When the emulsifier content exceeds 2.9 parts by weight relative to 100 parts by weight of the monomer mixture, problems such as reduced product quality due to the generation of foam in the molded product preparation process, reduced product properties due to emulsifier residues, and generation of wastewater containing emulsifiers may occur.
[0047] The starch may be one selected from the group consisting of natural starch, a derivative of the natural starch, amylose extracted from the natural starch, modified starch, dextrin, and a combination of two or more thereof, for example, dextrin, but not limited thereto.
[0048] The above-mentioned natural starch can be one selected from the group consisting of ordinary corn starch, waxy corn starch, high-amylose corn starch, rice starch, waxy rice starch, high-amylose rice starch, potato starch, sweet potato starch, tapioca starch, sorghum starch, wheat starch, sago starch, chestnut starch, soybean starch and a combination of two or more thereof, but is not limited thereto.
[0049] The modified starch may be one selected from the group consisting of hydroxypropyl starch, phosphate starch, oxidized starch, pregelatinized starch, octenyl succinate starch, acetate starch, and a combination of two or more thereof, but is not limited thereto.
[0050] The above-mentioned dextrin is a low molecular weight carbohydrate obtained by starch hydrolysis, which can be obtained by hydrolyzing natural starch with acid, heat, enzyme, etc., and commercial products can be purchased and used. The acid used for the above-mentioned hydrolysis can be hydrochloric acid, sulfuric acid, nitric acid or acetic acid, but is not limited thereto. The above-mentioned enzyme can be any enzyme, as long as it has the ability to hydrolyze starch, for example, it can be selected from the group consisting of α-amylase, β-amylase, glucoamylase, amyloglucosidase, isoamylase, fluoroalkanease, α-glucosidase and a combination of two or more thereof, but is not limited thereto.
[0051] The dextrose equivalent (DE) of the dextrin may be 8 to 22, for example, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 or a value between two of them. When the dextrose equivalent of the dextrin is less than 8, latex gelation may occur during the polymerization process, resulting in a decrease in the quality of the molded product. When the dextrin is greater than 22, viscosity decrease and browning may occur.
[0052] The molecular weight of the dextrin may be 1000 g / mol to 10000 g / mol, but is not limited thereto.
[0053] The content of the starch may be 0.25 to 2 times the content of the emulsifier. For example, the content of the starch may be 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2 times or a value between two of the values thereof. When the starch content is less than 0.25 times the emulsifier content, the mechanical stability and polymerization stability may decrease, and the effect of reducing the amount of emulsifier used may decrease, which may lead to problems such as foaming in the preparation process of the dip-molded product, resulting in a decrease in product quality, emulsifier residue causing a decrease in product properties, and the generation of wastewater containing emulsifiers. When the starch content is more than 2 times the emulsifier content, the tensile strength, elongation and other mechanical properties of the molded product and the product quality may decrease.
[0054] The additive may further include a molecular weight regulator. The molecular weight regulator may be a thiol, such as α-methylstyrene dimer, t-dodecyl mercaptan, n-dodecyl mercaptan, octylthiol, etc.; a halogenated hydrocarbon, such as carbon tetrachloride, dichloromethane, dibromomethane, etc.; a sulfur-containing compound, such as tetraethyl thiuram disulfide, dipentamethylene thiuram disulfide, diisopropylxanthogen disulfide, etc.; and one of the group consisting of a combination of two or more thereof, such as t-dodecyl mercaptan, but not limited thereto. The molecular weight modifier may be contained in an amount of 0.1 to 1.0 parts by weight relative to 100 parts by weight of the monomer mixture.
[0055] The step (c) is a step of preparing a copolymer latex by emulsion polymerization of the monomer mixture. The solid content concentration of the copolymer latex prepared by the polymerization may be in the range of 30% to 60%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60% or a range between two values thereof, wherein p The H value can be adjusted to 7 to 12, for example, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8, 10.0, 10.2, 10.4, 10.6, 10.8, 11.0, 11.2, 11.4, 11.6, 11.8, 12.0 or a range between two of these values, but is not limited thereto.
[0056] The polymerization in the above step (c) can be carried out in the range of 10°C to 90°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or a temperature between two of them.
[0057] The above step (c) may include: a step of polymerizing the above monomer mixture by adding a polymerization initiator; a step of stopping the polymerization by adding a polymerization terminator; and a step of obtaining a copolymer latex by removing unreacted monomers and adjusting the solid content concentration and pH value.
[0058] The polymerization initiator may be selected from inorganic peroxides such as sodium persulfate, potassium peroxodisulfate, ammonium persulfate, potassium superphosphate, hydrogen peroxide, etc.; organic peroxides such as t-butyl peroxide, cumene hydroperoxide, p-menthane hydroperoxide, di-tert-butyl peroxide, t-butylcumyl peroxide, acetyl peroxide, isobutyl peroxide, octanoyl peroxide, dibenzoyl peroxide, bis(3,5,5-trimethylhexanoyl) peroxide, 1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1,2-dimethyl-1 peroxide), tert-butylperoxyisobutyrate, etc.; and azobis isobutyronitrile, azobis-2,4-dimethyl valeronitrile, azobiscyclohexanecarbonitrile, azobisisobutyric acid (butyric acid) methyl, and a combination of two or more thereof, for example, potassium persulfate, but not limited thereto. The content of the polymerization initiator may be 0.02 to 1.5 parts by weight relative to 100 parts by weight of the monomer mixture.
[0059] The polymerization of the copolymer latex can be carried out by including an activator, which can be one selected from the group consisting of sodium formaldehyde sulfoxylate, sodium ethylenediamine tetraacetate, ferrous sulfate, dextrose, sodium pyrrolate, sodium sulfite, and a combination of two or more thereof, for example, sodium formaldehyde sulfoxylate, but not limited thereto. The content of the activator can be 0.01 to 0.3 parts by weight relative to 100 parts by weight of the monomer mixture.
[0060] The above-mentioned polymerization terminator can be added when the conversion rate of the above-mentioned polymerization reaction is more than 90%. For example, the above-mentioned polymerization terminator can be added when the conversion rate of the above-mentioned polymerization reaction is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.9% or a value between two of them.
[0061] The polymerization terminator may be one selected from the group consisting of aromatic hydroxydithiocarboxylic acids such as hydroxylamine, hydroxylaminesulfate, diethylhydroxylamine, hydroxylaminesulfonic acid and alkali metal ions thereof, sodium dimethyldithiocarbamate, hydroquinone derivatives, hydroxydiethylbenzene dithiocarboxylic acid, hydroxydibutylbenzenedithiocarboxylic acid, and combinations of two or more thereof, for example, sodium dimethyldithiocarbamate, but not limited thereto. The content of the polymerization terminator may be 0.02 to 1.5 parts by weight relative to 100 parts by weight of the monomer mixture.
[0062] The solid content concentration and pH value of the copolymer latex can be adjusted by adding additives such as a pH adjuster, an antioxidant, and a defoaming agent.
[0063] The pH adjuster may be a potassium hydroxide aqueous solution or an ammonia solution, but is not limited thereto.
[0064] The copolymer latex has excellent mechanical stability and polymerization stability, and thus can be used to prepare a stable latex composition for dip molding.
[0065] The method for preparing the latex composition for dip molding may further include: step (d), preparing the latex composition for dip molding by adding a vulcanizing agent, a vulcanization accelerator and a cross-linking agent to the copolymer latex.
[0066] The above-mentioned vulcanizing agent may include sulfur such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, and insoluble sulfur. Since these vulcanizing agents crosslink between polymer chains by attacking the π bonds in the conjugated double bonds of butadiene, in addition to imparting elasticity to the copolymer, the chemical resistance of the dip-molded product can also be improved. The above-mentioned vulcanizing agent content can be 0.1 to 3.0 parts by weight relative to 100 parts by weight of the above-mentioned copolymer latex.
[0067] The vulcanization accelerator may be selected from 2-mercaptobenzothiazole, 2,2-dithiobisbenzothioazole-2-sulfenamide, N-cyclohexylbenzothiazole-2-sulfenamide, 2-morpholinothiobenzothiazole, tetramethylthiurammonosulfide, tetramethylthiuramdisulfide, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, diphenylguanidine, The vulcanization accelerator may be selected from the group consisting of 1,2-di-o-tolylguanidine, 2,3-di-o-tolylguanidine, and a combination of two or more thereof, for example, zinc dibutyl dithiocarbamate, but not limited thereto. The content of the vulcanization accelerator may be 0.1 to 3.0 parts by weight relative to 100 parts by weight of the copolymer latex.
[0068] The crosslinking agent may be zinc oxide, but is not limited thereto. The content of the crosslinking agent may be 0.1 to 3.0 parts by weight relative to 100 parts by weight of the copolymer latex.
[0069] Latex composition for dip molding
[0070] A latex composition for dip molding according to another aspect of the present specification may be produced by the method for producing the latex composition for dip molding.
[0071] The solid content concentration of the latex composition for dip molding may be 10% to 30%, and the pH value may be 9 to 11, but is not limited thereto.
[0072] Dip molding
[0073] The dip-molded article according to another aspect of the present specification can be produced by subjecting the above-mentioned latex composition for dip molding to a dip molding process.
[0074] The above-mentioned dip-molded article has excellent mechanical properties such as tensile strength and elongation, and has a low defect rate and excellent quality such as hand feel, and can be applied to dip-molded articles in various fields.
[0075] The dip-molded product is one selected from the group consisting of medical gloves, agricultural and livestock product processing gloves, and industrial gloves, but is not limited thereto.
[0076] The embodiments of this specification are described in more detail below. However, the following experimental results only describe representative experimental results in the above embodiments, so the scope and content of this specification cannot be interpreted as being reduced or limited by the embodiments, etc. The various effects in the various embodiments of this specification that are not explicitly presented below will be specifically described in the corresponding parts.
[0077] Example 1
[0078] A 10L high-pressure reactor was prepared, which had an agitator, a thermometer, a cooler and a nitrogen inlet, and was capable of continuously adding various components such as monomers, emulsifiers and polymerization initiators. After replacing the reactor with nitrogen, a monomer mixture of 65 weight percent of 1,3-butadiene, 30 weight percent of acrylonitrile and 5 weight percent of methacrylic acid was added based on the total weight of the mixture. Afterwards, 1.4 weight parts of sodium dodecylbenzene sulfonate (SDBS), 0.7 weight parts of disodium alkyl diphenyloxide sulfonate (DPOS), 1 weight part of dextrin (Sanyo Co., Ltd.) with a molecular weight of 1000 g / mol to 10000 g / mol, 0.5 weight parts of tert-dodecyl mercaptan and 120 weight parts of ion exchange water were added to the reactor relative to 100 weight parts of the monomer mixture. After the temperature of the reactor was raised to about 25°C, 0.3 weight parts of potassium persulfate were added.
[0079] When the conversion rate reaches about 95%, 0.1 parts by weight of sodium dimethyldithiocarbamate is added to stop the polymerization reaction. Unreacted monomers are then removed by a deodorization process, and ammonia water, antioxidants, defoamers, etc. are added to obtain a carboxylic acid-modified nitrile copolymer latex having a solid content concentration of 45% and a pH value of 8.5.
[0080] Example 2
[0081] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 1 except that 3 parts by weight of dextrin was added.
[0082] Example 3
[0083] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 1 except that 1.0 part by weight of sodium dodecylbenzene sulfonate and 0.5 part by weight of disodium alkyl diphenyl ether sulfonate were added.
[0084] Example 4
[0085] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 3 except that 3 parts by weight of dextrin was added.
[0086] Comparative Example 1
[0087] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that 2.0 parts by weight of sodium dodecylbenzene sulfonate and 1.0 parts by weight of disodium alkyl diphenyl ether sulfonate were respectively added, and dextrin was not added.
[0088] Comparative Example 2
[0089] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 1 except that 5 parts by weight of dextrin was added.
[0090] Comparative Example 3
[0091] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 3 except that 5 parts by weight of dextrin was added.
[0092] Comparative Example 4
[0093] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 3 except that 10 parts by weight of dextrin was added.
[0094] Comparative Example 5
[0095] A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 3 except that 20 parts by weight of dextrin was added.
[0096] Table 1 below summarizes the contents of sodium dodecylbenzene sulfonate (SDBS), disodium alkyl diphenyl ether sulfonate (DPOS), and dextrin used in the polymerization of the carboxylic acid-modified nitrile copolymer latexes of Examples 1 to 4 and Comparative Examples 1 to 5.
[0097] Table 1
[0098]
[0099] Preparation Example
[0100] To 100 parts by weight of each carboxylic acid-modified nitrile copolymer latex prepared according to Examples 1 to 4 and Comparative Examples 1 to 5, 1.0 parts by weight of sulfur, 1.4 parts by weight of zinc oxide, and 0.6 parts by weight of zinc dibutyldithiocarbamate (ZDBC) were added, and a 4% aqueous potassium hydroxide solution and double distilled water were added to prepare a latex composition for dip molding having a solid content concentration of 18% and a pH of 10.0.
[0101] Experimental Example 1: Mechanical Property Evaluation
[0102] Dumbbell-shaped test pieces were prepared according to ASTM D-412 using each latex composition for dip molding prepared according to the above preparation examples. The test pieces were stretched at an elongation of 500 mm / min using a universal testing machine (UTM), and the mechanical properties were evaluated by measuring the tensile strength and elongation at break. Generally, the higher the tensile strength and elongation of the latex molded product, the better the evaluation of the dip quality.
[0103] Table 2 below shows the results of mechanical property evaluation of test pieces prepared from the latexes of Example 1 and Example 2 and Comparative Example 1 and Comparative Example 2.
[0104] Table 2
[0105] Classification Tensile strength(mPa) Elongation(%) Example 1 39.1 560 Example 2 38.3 553 Comparative Example 1 38.1 553 Comparative Example 2 29.7 535
[0106] Referring to Table 2 above, it can be confirmed that the tensile strength and elongation of the test pieces prepared from the latexes of Examples 1 and 2 are superior to those of the test piece prepared from the latex of Comparative Example 1. These results show that when starch is added in the polymerization step of the nitrile copolymer latex, the mechanical properties and impregnation quality of the molded product can be maintained or improved even if only 70% of the amount of emulsifier used in the past is added.
[0107] However, in Comparative Example 2, when the dextrin content was more than 4.9 parts by weight relative to 100 parts by weight of the monomer mixture, the tensile strength and elongation decreased, and it was confirmed that the mechanical properties of the test piece prepared from the latex of Comparative Example 1 could not be satisfied.
[0108] Table 3 below shows the results of mechanical property evaluation of test pieces prepared from the latexes of Example 3, Example 4, and Comparative Example 1, Comparative Example 3 to Comparative Example 5.
[0109] Table 3
[0110] Classification Tensile strength(mPa) Elongation(%) Example 3 39.9 563 Example 4 38.3 581 Comparative Example 1 38.1 553 Comparative Example 3 30.2 532 Comparative Example 4 25.1 489 Comparative Example 5 11.5 442
[0111] Referring to Table 3 above, it can be confirmed that the tensile strength and elongation of the test pieces prepared from the latexes of Examples 3 and 4 are superior to those of the test piece prepared from the latex of Comparative Example 1. These results show that when starch is added in the polymerization step of the nitrile copolymer latex, the mechanical properties and impregnation quality of the molded product can be maintained or improved even if only 50% of the amount of emulsifier used in the past is added.
[0112] However, in Comparative Examples 3 to 5, when the dextrin content exceeded 4.9 parts by weight relative to 100 parts by weight of the monomer mixture, the tensile strength and elongation decreased, and it was confirmed that the mechanical properties of the test piece prepared from the latex of Comparative Example 1 could not be satisfied.
[0113] Experimental Example 2: Mechanical Stability Evaluation
[0114] In order to evaluate the mechanical stability of each carboxylic acid-modified nitrile copolymer latex prepared according to the above Examples 1 to 4 and Comparative Examples 1 to 5, a latex stability test (maron test) was performed. The latex stability test uses a maron tester to put 30 g of a latex sample into a sample holder, and after applying a shear stress at a speed of 49 N and 1000 rpm for 1 minute, the weight of the generated coagulant is measured. It can be evaluated that the lower the weight of the coagulant generated during the latex stability test, the more excellent the mechanical stability.
[0115] Table 4 below shows the results of mechanical stability evaluation of the latexes of Example 1, Example 2 and Comparative Example 1, Comparative Example 2.
[0116] Table 4
[0117] Classification Condensate weight (ppm) Example 1 3600 Example 2 1800 Comparative Example 1 2790 Comparative Example 2 1000
[0118] Referring to Table 4 above, it can be confirmed that the mechanical stability of the latex of Example 2 is superior to that of the latex of Comparative Example 1. This result shows that when starch is added in the polymerization step of the nitrile copolymer latex, the mechanical stability of the latex is maintained or improved even if only 70% of the amount of emulsifier used in the past is added.
[0119] Table 5 below shows the results of mechanical stability evaluation of the latexes of Example 3, Example 4, and Comparative Examples 1, 3 to 5.
[0120] Table 5
[0121]
[0122]
[0123] Referring to Table 5 above, it can be confirmed that the mechanical stability of the latex of Example 4 is superior to that of the latex of Comparative Example 1. These results show that when starch is added in the polymerization step of the nitrile copolymer latex, the mechanical stability of the latex is maintained or improved even if only 50% of the amount of emulsifier used in the past is added.
[0124] Experimental Example 3: Evaluation of polymerization stability
[0125] In order to evaluate the latex polymerization stability of the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 5, the contamination degree of the reactor was measured after the completion of each polymerization process and evaluated using a 5-point method (5: very good; 4: good; 3: average; 2: poor; 1: very poor).
[0126] The polymerization stability evaluation results of Example 1, Example 2 and Comparative Example 1 and Comparative Example 2 are shown in Table 6 below.
[0127] Table 6
[0128] Classification Polymerization stability (5-point method) Example 1 3 Example 2 4 Comparative Example 1 2 Comparative Example 2 3
[0129] Referring to Table 6, it can be confirmed that the polymerization stability of Examples 1 and 2 is superior to that of Comparative Example 1. This result shows that when starch is added in the polymerization step of the nitrile copolymer latex, the polymerization stability in the latex polymerization process is maintained or improved even if only 70% of the amount of emulsifier used in the past is added.
[0130] The polymerization stability evaluation results of Example 3, Example 4, and Comparative Examples 1, 3 to 5 are shown in Table 7 below.
[0131] Table 7
[0132]
[0133]
[0134] Referring to Table 7, it can be confirmed that the polymerization stability of Examples 3 and 4 is superior to that of Comparative Example 1. This result shows that when starch is added in the polymerization step of the nitrile copolymer latex, the polymerization stability in the latex polymerization process is maintained or improved even if only 50% of the emulsifier used in the past is added.
[0135] The above description of the present invention is for illustrative purposes only, and persons with ordinary knowledge in the technical field to which the present invention belongs should understand that it can be easily transformed into other specific forms without changing the technical ideas or essential features of the present invention. Therefore, the embodiments described above should be understood to be exemplary and non-restrictive in all aspects. For example, the various components described in a single form can also be implemented in a dispersed manner, and the components described in a dispersed manner can also be implemented in a combined form.
[0136] The scope of the present specification should be reflected by the claims, and all changes and modifications derived from the meaning and scope of the claims and their equivalent concepts should be interpreted as being fully included in the scope of the present invention.
Claims
1. A method for preparing a latex composition for dip molding, characterized in that: include: Step (a), preparing a monomer mixture comprising a conjugated diene monomer, an ethylenically unsaturated nitrile monomer and an ethylenically unsaturated acid monomer; Step (b), adding additives including an inorganic solvent, an emulsifier and starch to the monomer mixture; and Step (c), preparing a copolymer latex by polymerizing the above monomer mixture, The emulsifier includes sodium dodecylbenzene sulfonate and disodium alkyl diphenyl ether sulfonate. The content of the emulsifier is 0.1 to 2.9 parts by weight relative to 100 parts by weight of the monomer mixture. The content of the starch is 0.1 to 4.9 parts by weight relative to 100 parts by weight of the monomer mixture.
2. The method for preparing the latex composition for dip molding according to claim 1, characterized in that: The conjugated diene monomer is one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, isoprene, and a combination of two or more thereof.
3. The method for preparing the latex composition for dip molding according to claim 1, characterized in that: The ethylenically unsaturated nitrile monomer is one selected from the group consisting of acrylonitrile, methacrylonitrile, fumaric acid nitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, and a combination of two or more thereof.
4. The method for preparing the latex composition for dip molding according to claim 1, characterized in that: The ethylenically unsaturated acid monomer is one selected from the group consisting of methacrylic acid, acrylic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, citraconic anhydride, styrene sulfonic acid, monobutyl fumarate, monobutyl maleate, mono-2-hydroxypropyl maleate, and a combination of two or more thereof.
5. The method for preparing the latex composition for dip molding according to claim 1, characterized in that: The starch is one selected from the group consisting of natural starch, derivatives of the natural starch, amylose extracted from the natural starch, modified starch, dextrin, and a combination of two or more thereof.
6. The method for preparing the latex composition for dip molding according to claim 5, characterized in that: The glucose equivalent value of the above dextrin is 8-22.
7. The method for preparing the latex composition for dip molding according to claim 1, characterized in that: The content of the starch is 0.25 to 2 times the content of the emulsifier.
8. A latex composition for dip molding, characterized in that: The method is prepared according to claim 1.
9. A dip-molded product, characterized in that: The latex composition for dip molding according to claim 8 is dip-molded to produce the product.
10. The dip-molded article according to claim 9, characterized in that The dip-molded product is one selected from the group consisting of medical gloves, agricultural and livestock product processing gloves, and industrial gloves.
